Family function and adolescent altruistic behavior: the chain mediating role of extraversion personality and perceived social support - Gao, Tao; Cui, Hongbo; Bi, Xiaoyan; Qing, Zaihua; Chen, Weiyu; Shi, Keke; Song, Meidan; Ma, Yankun (Frontiers in Psychology, 2024)
Introduction This study aimed to explore the relationship between family function and altruistic behavior in adolescents, while also investigating the potential mediating roles of extraverted personality and perceived social support. Methods Surveys were administered to high school students across various schools in Guangdong Province, utilizing the Family APGAR Questionnaire, Extraversion Personality Scale, Perceived Social Support Scale, and Altruistic Behavior Scale. A total of 972 valid questionnaires were collected for analysis. Results The findings revealed that family function did not directly predict altruistic behavior. However, extraverted personality and perceived social support were identified as mediators between family function and altruistic behavior. Furthermore, both extraverted personality and perceived social support acted as chain mediators in this relationship. Discussion These results emphasize the importance of considering family dynamics in understanding adolescent altruistic behavior and highlight the potential pathways through which family function influences altruistic tendencies. Promoting positive family environments and enhancing extraverted personality and perceived social support may facilitate the cultivation of altruistic behavior in adolescents.